2006
DOI: 10.1016/j.jcf.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A multi-method assessment of treatment adherence for children with cystic fibrosis

Abstract: The multi-method measurement approach provided unique information regarding rates of adherence for each disease condition by type of treatment component. Accurately measuring rates of treatment adherence for children with CF is an important step in developing effective interventions to influence these behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
228
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(242 citation statements)
references
References 26 publications
13
228
1
Order By: Relevance
“…There are also limitations to all adherence measures, including pharmacy refill records. Limitations of pharmacy refill records include that their accuracy may be affected by dosage changes and that they do not indicate whether medication is actually consumed according to the prescribed dosing schedule (43)(44)(45). However, as previously stated, prior research has found that RTRs who appropriately refill their IST are more likely to have desired IST serum concentrations, and therefore we believe pharmacy refill records are a reliable and valid measure of IST adherence (12).…”
Section: Discussionmentioning
confidence: 83%
“…There are also limitations to all adherence measures, including pharmacy refill records. Limitations of pharmacy refill records include that their accuracy may be affected by dosage changes and that they do not indicate whether medication is actually consumed according to the prescribed dosing schedule (43)(44)(45). However, as previously stated, prior research has found that RTRs who appropriately refill their IST are more likely to have desired IST serum concentrations, and therefore we believe pharmacy refill records are a reliable and valid measure of IST adherence (12).…”
Section: Discussionmentioning
confidence: 83%
“…In a recent US study, adult patients -of whom only half had performed airway clearance -reported a mean time spent on treatment activities of 108 minutes per day (Sawicki et al, 2009). Though very difficult to assess (Modi et al, 2006), treatment adherence is undoubtedly a key issue in CF (Eakin et al, 2011) and requires permanent assessment and support (Pendleton, 2000). There is no magic recipe, but this subject has to be bridged at every consultation, in an open manner, with empathy and as part of a 'therapeutic alliance' (Lask, 1994;Cohen-Cymberknoh et al, 2011).…”
Section: Many Other Challenges…mentioning
confidence: 99%
“…22 Adherence is a particular issue in young people as they are beginning to take over management of their illness. In addition, certain developmental issues (e.g.…”
Section: Adherencementioning
confidence: 99%
“…In order to improve adherence the initial task is to quantify the level of adherence for each treatment. 22 Determine the barriers to adherence These can be anything from simply not liking the taste of a particular medicine, to family reasons, to not prioritizing illness management to rebellion. Only then can the reasons be worked on.…”
Section: Determine the Level Of Adherencementioning
confidence: 99%